A Cost Effective and Preventive Approach to Avoid Integration Faults Caused by Mistakes in Distribution of Software Components. (15th December 2014) - Chaves, Luciano Lucindo
Abstract : In distributed software and hardware environments, ensuring proper operation of software is a challenge. The complexity of distributed systems increases the number of integration faults resulting from configuration errors in the distribution of components. Therefore, the main contribution of this work is a change in perspective, where integration faults (in the context of mistakes in distribution of components) are prevented rather than being dealt with through postmortem approaches. To this purpose, this paper proposes a preventive, low cost, minimally intrusive, and reusable approach. The generation of hash tags and a built-in version control for the application are at the core of the solution. Prior to deployment, the tag generator creates a list of components along with their respective tags, which will be a part of the deployment package. During production and execution of the application, on demand, the version control compares the tag list with the components of the user station and shows the discrepancies. The approach was applied to a complex application of a large company and was proven to be successful by avoiding integration faults and reducing the diagnosis time by 65%.